ANALYSIS OF DC MOTOR ROTATION SPEED ON THE BURNER STOVE FLAME USING OIL AS FUEL: A CASE STUDY IN TOMUANHOLLBUNG VILLAGE - Afandi, Adi Mas; Ananda, Ricki (STMIK Royal, 2024)
Abstract: Due to the successful conversion from LPG stoves to electric stoves, which are unsupported by the village’s electricity supply—averaging 450 watts—while government-provided stoves have a power rating of 900 watts, making them unsuitable for use in Tomuanhollbung Village. To address this issue, the research team designed a stove that uses waste oil (35,000 kJ/kg) and incorporated embedded system technology, utilizing the French design research method. The research results indicated that by using a DC motor with specifications of 12VDC/3A, 3800 rpm, and a valve diameter of 9.7 x 9.5 x 3.3 cm, a power output of 36W was achieved, with a pressure of 288.7 Pa or 0.00289 bar and an angular velocity of 398.1 rad/s. When the burner stove was first ignited, the flame appeared yellow. With a voltage of 3.7VDC/3A, it produced a rotation of 3795 rpm, a yellow flame, a flame height of 8 cm from the stove, and a flame width diameter of approximately 18 cm. At a voltage of 3.7VDC, the pressure measured 0.000964 bar, with a flame temperature of 275°C (as measured by an infrared sensor). A voltage of 7.4VDC resulted in a pressure of 0.0192 bar and a flame temperature of 350°C, while a voltage of 11.8VDC produced a pressure of 0.0289 bar with a maximum flame temperature of 420°C. For fuel consumption over 10 minutes at 3.7VDC/3A, the flame height reached 7-10 cm, with a wind pressure of 0.000964 bar and a fuel consumption of 0.237 grams. Keywords : embedded system burner stove; microcontroller; snail dc motor. Abstrak: Dilatar belakangi masalah kelangkaan elpiji didesa tomuanhollbung, serta tidak berhasilnya konversi kompor elpiji menuju kompor listrik karena daya listrik rumah masyarakat berdaya 450wat, daya kompor pemerintah 900watt, sehingga tidak bisa digunakan. Dari masalah tersebut, tujuan utama penelitian ini merancang kompor berbahan bakar oli bekas, yang mampu mengatasi masalah kelangkaan gas elpiji dan tidak terpakainya kompor dari pemerintah psat. Metode penelitian ini menggnakan metode prototype sehingga menghasilkan satu produk kompor burner dengan mengatur kecepatan motor DC. Hasil penelitian mendapati data pengujian mendapati bahwa dengan menggunakan motor DC Keong spesifikasi tegangan 12VDC/3A, 3800 rpm, dengan diameter katup 9,7 x 9.5 x 3.3cm menghasilkan daya 36W, dengan tekanan 288.7Pa atau 0.00289bar kecepatan sudut 398.1 rad/s. Ketika kompor burner pertama kali dinyalakan, warna api berwarna kunig. Jika tegangan 3.7VDC/3A akan menghasilkan putaran 3795rpm nyala api kuning, tinggi api 8cm dari tunggku kompor, dan diameter lebar keluarnya api dari tungku berkisar 18cm. Tegangan 3,7VDC maka menghasilkan tekanan 0.000964bar, nyala api 275 0C (pembacaan sensor infrared). Tegangan 7.4VDC menghasilkan tekanan 0.0192 bar, nyala api 350 0C, dan Tegangan 11.8 VDC tekanan 0.0289 bar, nyala api maksimal 420 0C. Untuk konsumsi bahan bakar selama 10 menit, dengan tegangan 3.7VDC/3A mendapati nyala api setinggi 7-10 cm, tekanan angin senilai 000964 bar dan konsumsi bahan bakar 0.237 gram. Kesimpulan penelitian ini mendapati bahwa nyala api kompor burner bisa di atur seperti nyala api kompor elpiji pada umum nya. Kata kunci: kompor burner embedded system, microcontroller, motor dc keong.